Post-traumatic Stress Disorder and Major Depressive Disorder: Impact of Mass Shootings - Olszańska, Monika; Hakało, Dominika; Suprun, Tomasz; Kałuska, Joanna; Ignatiuk-Chilkiewicz, Marta; Nowicka, Katarzyna; Klimek, Wiktor; Sokół, Aleksandra; Mościszko, Klaudia; Majewska, Maria (Quality in Sport, 2025)
Introduction: Post-traumatic stress disorder (PTSD) is a debilitating mental health condition that may develop following exposure to severe traumatic events, including mass shootings. Although less than 10% of those exposed ultimately develop PTSD, a substantial proportion of patients, up to 52%, also meet the criteria for major depressive disorder (MDD), which is associated with more severe symptoms and poorer treatment outcomes. Materials and methods: A review of chosen literature from PubMed and Google Scholar was conducted, using key words including "PTSD", "MDD", "comorbidity" "symptoms", "treatment". Summary: This review synthesises recent studies examining the prevalence, symptom profiles, and treatment responses in individuals with comorbid PTSD and MDD following mass shootings. Findings indicate that PTSD prevalence varies considerably according to trauma type and exposure level, with direct and indirect exposures exerting distinct influences on symptomatology. Conclusions: Comorbid MDD appears to exacerbate functional impairments and may attenuate the effectiveness of standard PTSD interventions. Evidence suggests that early intervention, comprehensive assessment of trauma and risk factors, and tailored therapeutic approaches, including sequential treatment strategies, are critical in mitigating long-term psychological and functional impairments in this population. These results underscore the need for improved screening, intervention, and support systems for survivors of mass shootings to enhance recovery and long-term outcomes.